Aspek Pidana dalam Sengketa Tanah di Indonesia: Analisis Normatif dan Praktik Penegakan Hukum - Mahmud, Mustakim (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2025)
Land disputes in Indonesia often have implications not only in the realm of civil and administrative law, but also involve aspects of criminal law. Phenomena such as land grabbing, certificate forgery, and criminal acts of corruption related to the transfer of land rights demonstrate the intersection between agrarian law and criminal law. This article aims to analyze the forms of criminal acts in land disputes, the challenges of law enforcement, and efforts to resolve them. The research method used is a normative juridical approach through the analysis of legislation, doctrine, and court decisions. The results of the study show that criminal aspects are involved in land disputes when there is malicious intent (mens rea) on the part of certain parties, for example, by falsifying land documents or carrying out forced encroachment. The resolution of land disputes through criminal channels requires caution so as not to blur the line between purely civil disputes and criminal acts.